Sinusoidal and Relaxation Wide Range Voltage Controlled Oscillators - Milan Stork (Communications - Scientific letters of the University of Zilina, 2015)
This paper presents a sinusoidal Wien-bridge and square wave wide range voltage controlled oscillators. The square wave oscillator is based on relaxation (Schmitt trigger) topology. All described oscillators have potential use in different applications, e.g. phase locked loops, modulation and detection. The frequency changing is based on optically coupled resistor with 100 dB dynamic range. The oscillators were constructed and measured. The new method for amplitude control for quadrature oscillator is also described.